MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL TEAM GAMES TOURNAMENT (TGT) KELAS IVB DI SDN 23 PALEMBANG - Aaliyah, Nadianti Beka; Riswan Jaennudin; Faiz Amali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the learning outcomes of class IV B students at SD N 23 Palembang in the mathematics subject of whole numbers through the teams games tournament (TGT) learning model. The Teams Games Tournament (TGT) learning model is cooperative learning that involves academic tournaments, and uses quizzes and a scoring system, where students compete to represent their team with members of other teams in academic performance. The research method used in this research is Classroom Action Research (PTK) which consists of pre-cycle, cycle I and cycle II with 4 stages, namely planning, action, observation and reflection. The subjects in this research were class IV B students at SD Negeri 23 Palembang, totaling 23 students consisting of 13 men and 10 women. Data collection in this research used tests with data analysis using the percentage formula. The research results show that the application of the Teams Games Tournament (TGT) learning model can improve mathematics learning outcomes. This can be seen from the increase in the percentage of completeness of student learning outcomes in mathematics subjects from pre-school by 30%, increasing in cycle I to 57% and increasing in cycle II to 87%. Thus, the application of the Teams Games Tournament model has proven to be effective in improving student learning outcomes in mathematics learning whole number material for class IV SD Negeri 23 Palembang